2006
DOI: 10.1073/pnas.0511102103
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint functions are required for normal S-phase progression in Saccharomyces cerevisiae RCAF- and CAF-I-defective mutants

Abstract: The chromatin-assembly factor I (CAF-I) and the replication-coupling assembly factor (RCAF) complexes function in chromatin assembly during DNA replication and repair and play a role in the maintenance of genome stability. Here, we have investigated their role in checkpoints and S-phase progression. FACS analysis of mutants lacking Asf1 or Cac1 as well as various checkpoint proteins indicated that normal rates of S-phase progression in asf1 mutants have a strong requirement for replication checkpoint proteins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 43 publications
8
40
0
Order By: Relevance
“…The cell cycle distribution was followed using the budding index, which uses the bud morphology of normal log-phase cells to identify cells in G 1 phase (no bud), S phase (small bud), and G 2 /M phase (large bud). We also counted cells with aberrant morphology, which typically consist of cells with grossly elongated or multiple buds and have been observed in strains with alterations in the timing of cell cycle transitions, DNA replication defects, and uncoupling of replication defects from checkpoint responses (56,64,73,74). We observed decreased proportions of G 1 -and S-phase cells, along with an increased fraction of cells with aberrant morphologies in strains where the rnh203⌬ mutation was combined with the asf1⌬, esc2⌬, mgs1⌬, mph1⌬, mre11⌬, rad50⌬, rad52⌬, or xrs2⌬ mutation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell cycle distribution was followed using the budding index, which uses the bud morphology of normal log-phase cells to identify cells in G 1 phase (no bud), S phase (small bud), and G 2 /M phase (large bud). We also counted cells with aberrant morphology, which typically consist of cells with grossly elongated or multiple buds and have been observed in strains with alterations in the timing of cell cycle transitions, DNA replication defects, and uncoupling of replication defects from checkpoint responses (56,64,73,74). We observed decreased proportions of G 1 -and S-phase cells, along with an increased fraction of cells with aberrant morphologies in strains where the rnh203⌬ mutation was combined with the asf1⌬, esc2⌬, mgs1⌬, mph1⌬, mre11⌬, rad50⌬, rad52⌬, or xrs2⌬ mutation ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The budding index, defined as the ratio of the number of individuals bearing buds to the total cell number, was determined microscopically, with individual cells bearing buds being counted as one cell (56). Cells were grown in YPD medium to log phase, sonicated, and examined by light microscopy, and the numbers of single cells, small-budded cells (bud smaller than onethird of the mother cell), large-budded cells (bud equal to or larger than one-third of the mother cell), and other cells (cells with protruded or multiple buds) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…These data suggest that DNA damage generated by perturbation of the replisome requires Rtt109 and H3 Lys-56-Ac for survival. Many of these phenotypes are shared by mutants that lack Asf1, an H3/H4 histone binding chaperone (13,(35)(36)(37). This phenotypic similarity was recently explained by the finding that Asf1 is also required for H3 Lys-56-Ac (13).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using this approach have demonstrated that there are eight pathways for suppressing these chromosomal aberrations, while six pathways promote GCR formation. The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%